2014
DOI: 10.1371/journal.pone.0108049
|View full text |Cite
|
Sign up to set email alerts
|

EGF Up-Regulates miR-31 through the C/EBPβ Signal Cascade in Oral Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most prevalent carcinomas worldwide. MicroRNAs (miRNAs) are short, non-coding RNAs that regulate gene expression and modulate physiological or pathological processes including OSCC carcinogenesis. miR-31 has been found to be up-regulated in OSCC and to act as an oncogenic miRNA. However, the molecular mechanism underlying miR-31 up-regulation in OSCC is still obscure. The activation of epidermal growth factor receptor (EGFR) signaling axis plays key roles in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 41 publications
2
53
1
Order By: Relevance
“…Upregulation of hsa-mir-31-5p is found in HNSCC and OSCC tissue, oral swirls, plasma of patients with OSCC, and HNSCC and OSCC cell lines. 66 In addition to this, several studies highlight the potential role of hsa-mir-31-5p as a diagnostic and prognostic marker: Severino et al and Siow et al found a higher hsa-mir-31-5p expression level in N0 OSCC cases, thus indicating hsa-mir-31-5p may be a favorable prognostic factor. 14,33, 34 Lu et al found that the upregulation of hsa-mir-31-5p in OSCC is inter alia caused through stimulation of epithelial growth factor I.…”
Section: Hsa-mir-31-5pmentioning
confidence: 98%
See 1 more Smart Citation
“…Upregulation of hsa-mir-31-5p is found in HNSCC and OSCC tissue, oral swirls, plasma of patients with OSCC, and HNSCC and OSCC cell lines. 66 In addition to this, several studies highlight the potential role of hsa-mir-31-5p as a diagnostic and prognostic marker: Severino et al and Siow et al found a higher hsa-mir-31-5p expression level in N0 OSCC cases, thus indicating hsa-mir-31-5p may be a favorable prognostic factor. 14,33, 34 Lu et al found that the upregulation of hsa-mir-31-5p in OSCC is inter alia caused through stimulation of epithelial growth factor I.…”
Section: Hsa-mir-31-5pmentioning
confidence: 98%
“…Samples were tested for 16 HPV subtypes (HPV 6,11,16,18,31,33,35,39,45,51,52,56,58,59,66, and 68) using multiplexbased fluorescence PCR (F-HPV typing™, Genomed Diagnostics AG, Paisley, United Kingdom). Samples were tested for 16 HPV subtypes (HPV 6,11,16,18,31,33,35,39,45,51,52,56,58,59,66, and 68) using multiplexbased fluorescence PCR (F-HPV typing™, Genomed Diagnostics AG, Paisley, United Kingdom).…”
Section: Hpv16mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are noncoding RNAs that downregulate the expression of targeted genes by binding to the specific sequences in the 3′untranslated region (UTR) of the transcript via seed sequences . Many miRNAs are involved in the neoplastic process associated with HNSCC . Our previous studies have shown that there is drastic upregulation of miR‐31 in HNSCC .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, only CEBPB retained after bonferroni adjustment. As an important regulator, CEBPB is implicated in various biological activities, including adiposeness, inflammatory responses, cell differentiation and proliferation, and cancer progression, such as breast cancer, oral carcinomas, and esophageal squamous cell carcinomas . Fang et al .…”
Section: Discussionmentioning
confidence: 99%